Green infrastructure and public policies: An international review of green roofs and green walls incentives. (July 2020) - Liberalesso, Tiago; Oliveira Cruz, Carlos; Matos Silva, Cristina; Manso, Maria
Highlights: Green infrastructure (GI) is being used to mitigate dense urban areas impacts. Incentive policies have great impact on green infrastructure implementation. Some green roofs/walls included as GI have high upfront installation costs. GI incentive policies are mainly concentrated in Europe and North America. Most used incentive policies are financial subsidies and obligations by law. Abstract: Worldwide, green infrastructure is increasingly used to mitigate the impacts of dense urban areas, contributing towards the naturalization of the built environment. However, for investors, these systems often emerge as requiring substantial upfront cost (high installation costs) and, depending on the solution, might also have significant maintenance costs. On the other hand, policymakers are placing green infrastructure on the agenda, as a solution to consider in urban planning and design. There is a mismatch between the economic/social/environmental value of green infrastructure and their financial analysis. As the quantified benefits of these solutions may not compensate the high implementation costs, discouraging building owners to invest in them. The alignment of both expectations, public and private agents, regarding the development of green infrastructure, is done through the use of incentives, with distinct configurations and nature, that promote and facilitate the adoption of green infrastructure by private investors. This research aims to identify and analyse the incentive policies used by several municipalities to promote the installation of green roofs and/or green walls. The data set includes 113 cities in 19 countries. The incentive policies were classified into six different categories: tax reductions, financing, construction permit, sustainability certification, obligations by law and agile administrative process. The results show that incentive policies are mainly concentrated in Europe and North America, and most incentive policies focus on the promotion of green roofs, as no exclusive incentive policies for the promotion of green walls were found. From all incentive policies studied, financial subsidies and obligations by law are the most used ways to promote green infrastructure worldwide.